2019
DOI: 10.1186/s40164-019-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Achievements and futures of immune checkpoint inhibitors in non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) has been threatening human health for years. Cytotoxicity-based chemotherapy seems to reach plateau in NSCLC treatment. Immunotherapy with immune checkpoint inhibitors (ICIs) against programmed cell death 1 (PD-1/L1) axis are to provide long-term survival benefits for wild-type advanced NSCLC patients with acceptable adverse effects. Though beneficiary population is limited from monotherapy, combination strategies are expanding indicators. Retrospective evidences suggested IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…As the leading cause of cancer‐related deaths worldwide, lung cancer is categorized into non‐small cell lung cancer (NSCLC) and small cell lung cancer with the former occupying 85% of all lung cancer cases . Since the initial presentation, NSCLC patients undergo multiple clinical and molecular examinations before implementation of treatment including clinical work‐up, biopsy, and molecular testing, and apart from surgery, platinum‐based chemotherapy, target therapy, and the novel immune therapy are administered accordingly .…”
Section: Introductionmentioning
confidence: 99%
“…As the leading cause of cancer‐related deaths worldwide, lung cancer is categorized into non‐small cell lung cancer (NSCLC) and small cell lung cancer with the former occupying 85% of all lung cancer cases . Since the initial presentation, NSCLC patients undergo multiple clinical and molecular examinations before implementation of treatment including clinical work‐up, biopsy, and molecular testing, and apart from surgery, platinum‐based chemotherapy, target therapy, and the novel immune therapy are administered accordingly .…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, Immune checkpoint (IC) blockade by inhibitors of the programmed cell death 1 (PD-1) and PD-1 ligand 1 (PD-L1) has significantly improved clinical outcome for a variety of solid tumors [1,2], while little is known about the role of ICs in leukemia [3]. Previous reports have shown that higher numbers of PD-1 + T cells are related to poor outcome for patients with acute myeloid leukemia (AML) [3].…”
mentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs), such as monoclonal antibodies (mAbs) against PD‐1 or PD‐L1, restored tumor‐specific T‐cell immunity and inhibited tumor growth in preclinical models . Initial clinical investigations in patients with metastatic or advanced non–small cell lung cancer (aNSCLC) demonstrated efficacy in the second‐ and third‐line settings after failure of standard chemotherapy . Since then, evidence from multiple randomized trials has led to the approval of two ICIs, pembrolizumab (anti‐PD‐1) and atezolizumab (anti‐PD‐L1), for the first‐line treatment of aNSCLC as monotherapy or as part of combination chemoimmunotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…1 Initial clinical investigations in patients with metastatic or advanced non-small cell lung cancer (aNSCLC) demonstrated efficacy in the second-and thirdline settings after failure of standard chemotherapy. 2 Since then, evidence from multiple randomized trials has led to the approval of two ICIs, pembrolizumab (anti-PD-1) and atezolizumab (anti-PD-L1), for the first-line treatment of aNSCLC as monotherapy or as part of combination chemoimmunotherapy. [3][4][5][6] Nivolumab (anti-PD-1) was also studied as first-line monotherapy for aNSCLC (PD-L1 greater than 5%) but was not approved because it did not significantly improve progression-free survival (PFS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%